2015
DOI: 10.1097/dss.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rate and Patient Satisfaction of CO2 Laser Evaporation of Lesions in Patients With Hidradenitis Suppurativa

Abstract: This study supports the claim that CO2 laser treatment is an effective modality for recurrent HS lesions in a majority of patients. The authors identified obesity as a risk factor for recurrence. Self-reported satisfaction is high, and only 3 of 58 report no change in the condition. None reported a worsening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 22 publications
(10 reference statements)
0
49
0
7
Order By: Relevance
“…Obesity was only associated with delayed wound healing. Previous studies suggested that CO 2 laser is an effective treatment option, and that obesity was associated with higher recurrence rates …”
Section: Discussionmentioning
confidence: 99%
“…Obesity was only associated with delayed wound healing. Previous studies suggested that CO 2 laser is an effective treatment option, and that obesity was associated with higher recurrence rates …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to flare, the terms recurrence and relapse were used more frequently in the literature and had a higher proportion of studies with a definition (Table S1; see Supporting Information). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Again, in contrast to flare, recurrence or relapse were more frequently associated with an increase in HS activity after a surgical intervention. Of the 19 studies that defined either relapse or recurrence, six (32%, six of 19) used the term in association with a medical intervention, while the majority (68%, 13 of 19) used the terms for a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been shown to influence the effect of treatments. In HS disease severity appears to co‐vary with BMI and recurrence rates after CO 2 laser surgery are better in patients with low BMI compared with patients with higher BMI . The weight of patients may also prove to be an important factor when treating patients with HS with tumour necrosis factor (TNF)‐α inhibitors .…”
Section: Discussionmentioning
confidence: 99%
“…In HS disease severity appears to co-vary with BMI and recurrence rates after CO 2 laser surgery are better in patients with low BMI compared with patients with higher BMI. 23 The weight of patients may also prove to be an important factor when treating patients with HS with tumour necrosis factor (TNF)-a inhibitors. 24 When using anti-TNF-a agents in chronic inflammatory skin diseases such as psoriasis, 25 optimal responses are less frequently observed in patients with psoriasis with increasing weight, especially above 100 kg, when using fixed standard doses.…”
Section: Discussionmentioning
confidence: 99%